Strategi Pengembangan Sport tourism di Kek Mandalika Dalam Mewujudkan Sinergi Dengan Masyarakat Lokal Desa Kuta, Mertak, Sengkol Kecamatan Pujut, Kabupaten Lombok Tengah - Hamid, Abdul; Satiadji, Amirosa Ria; Zuraida, Lukia (Jurnal Ilmiah Global Education, 2025)
This study aims to formulate development strategies for sport tourism in the Mandalika Special Economic Zone (SEZ), focusing on synergy with local communities in the villages of Kuta, Mertak, and Sengkol, Pujut District, Central Lombok. Despite Mandalika SEZ’s great potential through hosting international events such as MotoGP, the involvement of local communities in sport tourism activities remains limited. A qualitative approach was applied, with data collected through in-depth interviews, observation, and documentation. Data analysis employed SWOT and PESTEL frameworks, supported by triangulation to ensure data validity. The findings indicate that sustainable sport tourism development requires four key strategies: (1) collaboration between event organizers and local communities, (2) capacity building through training and digital promotion systems, (3) the formulation of standard operating procedures (SOPs) for community involvement and partnership regulations, and (4) legal and economic protection for local stakeholders. These strategies are implemented through community asset mapping, needs-based training, the formation of communication forums, and participatory evaluation. This study contributes to the development of a participatory sport tourism model within a special economic zone framework, positioning local communities as active agents of development.